2011
DOI: 10.1016/j.pec.2010.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Seniors’ perceptions of prescription drug advertisements: A pilot study of the potential impact on informed decision making

Abstract: Objective To conduct a pilot study exploring seniors' perceptions of direct-to-consumer advertising (DTCA) of prescription drugs and how the advertisements might prepare them for making informed decisions with their physicians. Methods We interviewed 15 seniors (ages 63-82) individually after they each watched nine prescription drug advertisements recorded from broadcast television. Grounded Theory methods were used to identify core themes related to the research questions. Results Four themes emerged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
1
11
0
1
Order By: Relevance
“…In prior research, consumers usually have reported neutral to positive attitudes toward DTC advertising [42]. In contrast, providers more often disapprove of DTC advertisements [43], perhaps due to concerns about biased information or patients making inappropriate medication demands [44]. Yet some providers have cited DTC advertising as having a possible benefit of increasing patient-provider communication about treatment options [43, 45], which aligns with feedback in the current study.…”
Section: Discussionsupporting
confidence: 73%
“…In prior research, consumers usually have reported neutral to positive attitudes toward DTC advertising [42]. In contrast, providers more often disapprove of DTC advertisements [43], perhaps due to concerns about biased information or patients making inappropriate medication demands [44]. Yet some providers have cited DTC advertising as having a possible benefit of increasing patient-provider communication about treatment options [43, 45], which aligns with feedback in the current study.…”
Section: Discussionsupporting
confidence: 73%
“…For instance, older individuals are more vulnerable to DTCA than are younger individuals because they tend to obtain less information from the advertisements 30 and are more likely to misinterpret information on the effectiveness of advertised drugs. 37 The misinterpretation of a drug’s effectiveness can complicate the physician–patient relationship if the patient requests the advertised drug. 37 While younger adults might also misinterpret information in DTCA, older adults are more likely to have several medical conditions requiring more prescription drugs and are therefore more likely to be effected by communication gaps in drug advertisements.…”
Section: Introductionmentioning
confidence: 99%
“… 37 The misinterpretation of a drug’s effectiveness can complicate the physician–patient relationship if the patient requests the advertised drug. 37 While younger adults might also misinterpret information in DTCA, older adults are more likely to have several medical conditions requiring more prescription drugs and are therefore more likely to be effected by communication gaps in drug advertisements. 30 Less educated and lower income individuals may obtain less information from drug advertisement and may be more vulnerable than others to the medication information gap.…”
Section: Introductionmentioning
confidence: 99%
“…Veicular orientação sobre descarte nas campanhas publicitárias de medicamentos foi a estratégia avaliada como pior em todos os critérios: de difícil mediação e fiscalização, complexa, de alto custo e de baixas adesão e abrangência. A rejeição das campanhas publicitárias de medicamentos pelos pesquisados pode estar relacionada com efeitos considerados negativos dessa estratégia: as propagandas de medicamentos não fornecem informações suficientemente detalhadas, e algumas informações podem ser mal interpretadas (COX;COX, 2010;GRENARD et al, 2011).…”
Section: Discussionunclassified